Profiling of adhesive-related genes in the freshwater cnidarian Hydra magnipapillata by transcriptomics and proteomics. Issue 9 (20th October 2016) - Rodrigues, Marcelo; Ostermann, Thomas; Kremeser, Leopold; Lindner, Herbert; Beisel, Christian; Berezikov, Eugene; Hobmayer, Bert; Ladurner, Peter
Abstract: The differentiated ectodermal basal disc cells of the freshwater cnidarian Hydra secrete proteinaceous glue to temporarily attach themselves to underwater surfaces. Using transcriptome sequencing and a basal disc-specific RNA-seq combined with in situ hybridisation a highly specific set of candidate adhesive genes was identified. A de novo transcriptome assembly of 55, 849 transcripts (>200 bp) was generated using paired-end and single reads from Illumina libraries constructed from different polyp conditions. Differential transcriptomics and spatial gene expression analysis by in situ hybridisation allowed the identification of 40 transcripts exclusively expressed in the ectodermal basal disc cells. Comparisons after mass spectrometry analysis of the adhesive secretion showed a total of 21 transcripts to be basal disc specific and eventually secreted through basal disc cells. This is the first study to survey adhesion-related genes in Hydra . The candidate list presented in this study provides a platform for unravelling the molecular mechanism of underwater adhesion of Hydra.